Development of crop climate calendars for high-value crops in Atok, Benguet: Report from preliminary co-learning and co-development engagements with agricultural stakeholders in Benguet province - Sonny N. Domingo; Anna Jennifer L. Umlas; Katrina Mae C. Zuluaga (Philippine Institute for Development Studies (PIDS), 2020)
Crop climate calendars augment traditional crop calendars by not only specifying planting and harvest schedules but also describing phenological states, cultivation practices and weather and climate requirements that any crop faces throughout a cropping season. The case to document this information in Benguet is compelling: The mountainous province experiences a unique microclimate and phenomena such as frost and hail and derives income from the cultivation of high value crops such as carrots, cabbage and potatoes amidst this. The researchers conducted focus group discussions with the municipal agriculturalists and farmer leaders in Atok, Benguet to understand their experiences and from there construct their crop climate calendar. The calendars produced in this exercise may serve as a solid foundation for the analysis of the community's climate-sensitive agricultural decisions.
Keywords: 330; crop climate calendar; high value crops; weather and climate information; decision analysis; agriculture